Interacción entre genotipos de frijol y aislamiento de Rhizoctonia solani Kuhn, heredabilidad de la resistencia a la mustia hilachosa Thanatephorus cucumeris (Frank) (Donk) en cultivares y poblaciones F¹ y F² de frijol común Phaseolus vulgaris. - Rodríguez, E.; García, A.; Frias, G; Beebe, Stephen E. (1995)
Interaction among bean genotypes and isolation of Rhizoctonia solani Kuhn. heritability of resistance to web-blight Thanatephorus cucumeris (Frank) (Donk) in cuItivars and F1 and F2 populations of common bean (Phaseolus vulgaris L. Meso-american and Andean eommon bean genotypes were inoeulated with mycellium of Thanatephorus cucumeris (Frank), Donk to determine: 1- The interaction among different isolations of Rhizoclonia solani, Kuhn and bean genotypes from two genetic pools, 2- the heritability of resistance to web-blight and 3- the existing genic completion between the meso-american and Andean pools, respeetively. The results found in this experiment were as follows : the strains vary depending of the origin site. Thus, the Dominican Republic and Colombian strains cause a lesser damage to the bean plants. The Panama # 1 isolation is moderately slow, and the Panama #2 and Costa Rica caused the largest damage to the crop. The RS-32-Cr strain was the most virulent of all. The heritabiJity shown by crossing was high which indieates that there is genic completion between the meso-ameriean and the Andean pools, respectively. The erossing of of AFR-251 x BAT-1155, in a direct and reciprocal way, showed differences in the F1 and the F2, indicating that the resistance to the disease is controlled by cytoplasmie genes as by nuclear genes. The type of resistance shown by the different evaluated crosses was horizontal and not vertical resistance.